Effect of Thermospermine on the Growth and Expression of Polyamine-Related Genes in Rice Seedlings - Minaho Miyamoto; Satoshi Shimao; Wurina Tong; Hiroyasu Motose; Taku Takahashi (Plants, 2019)
A mutant defective in the biosynthesis of thermospermine, acaulis5 (acl5), shows a dwarf phenotype with excess xylem vessels in Arabidopsis thaliana. Exogenous supply of thermospermine remarkably represses xylem differentiation in the root of seedlings, indicating the role of thermospermine in proper repression of xylem differentiation. However, the effect of thermospermine has rarely been investigated in other plant species. In this paper, we examined its effect on the growth and gene expression in rice seedlings. When grown with thermospermine, rice seedlings had no clearly enlarged metaxylem vessels in the root. Expression of OsACL5 was reduced in response to thermospermine, suggesting a negative feedback control of thermospermine biosynthesis like in Arabidopsis. Unlike Arabidopsis, however, rice showed up-regulation of phloem-expressed genes, OsHB5 and OsYSL16, by one-day treatment with thermospermine. Furthermore, expression of OsPAO2 and OsPAO6, encoding extracellular polyamine oxidase whose orthologs are not present in Arabidopsis, was induced by both thermospermine and spermine. These results suggest that thermospermine affects the expression of a subset of genes in rice different from those affected in Arabidopsis.